2010
DOI: 10.1161/strokeaha.110.595330
|View full text |Cite
|
Sign up to set email alerts
|

The Carotid Revascularization Endarterectomy Versus Stenting Trial (CREST)

Abstract: Background and Purpose-Carotid artery stenosis causes up to 10% of all ischemic strokes. Carotid endarterectomy (CEA) was introduced as a treatment to prevent stroke in the early 1950s. Carotid stenting (CAS) was introduced as a treatment to prevent stroke in 1994. Methods-The Carotid Revascularization Endarterectomy versus Stenting Trial (CREST) is a randomized trial with blinded end point adjudication. Symptomatic and asymptomatic patients were randomized to CAS or CEA. The primary end point was the composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
246
2
11

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 338 publications
(267 citation statements)
references
References 25 publications
8
246
2
11
Order By: Relevance
“…We verified that 36.2% (US$ 645,570.10) of the total spent in each surgical procedure corresponds to the cost of the intensive care unit after CEA and 11% (US$ 30,645.78) after CAS. The Carotid Revascularization Endarterectomy versus Stenting Trial (CREST) 35 , conducted in the USA, showed that the initial cost with CAS is higher, costing an average of US$ 1,025 more per patient when compared with CEA, which corroborates Brazilian data.…”
Section: Economic Aspectssupporting
confidence: 72%
See 1 more Smart Citation
“…We verified that 36.2% (US$ 645,570.10) of the total spent in each surgical procedure corresponds to the cost of the intensive care unit after CEA and 11% (US$ 30,645.78) after CAS. The Carotid Revascularization Endarterectomy versus Stenting Trial (CREST) 35 , conducted in the USA, showed that the initial cost with CAS is higher, costing an average of US$ 1,025 more per patient when compared with CEA, which corroborates Brazilian data.…”
Section: Economic Aspectssupporting
confidence: 72%
“…These results differ from the reality found in places such as USA, Canada and Europe. The risk of perioperative mortality in the CREST study ranged from a 0.3% for CEA and 0.7% for CAS [34][35][36] . In Brazil, not only are the mortality rates for both types of treatment higher, but also the inequalities in the risk of death between the two surgical modalities are not reproduced.…”
Section: Surgical Resultsmentioning
confidence: 99%
“…However, most relevant clinical trials demonstrated that the rate of composite outcomes (disability stroke, myocardial infarction, or death) was not significantly different between patients treated with carotid artery stenting (CAS) and CEA during short-, intermediate-, and long-term follow-up (14)(15)(16)(17). These findings underscore that CAS in combination with the use of distal protective devices is non-inferior to CEA in the treatment of patients with symptomatic severe carotid artery stenosis.…”
Section: Introductionmentioning
confidence: 98%
“…17,27) Although favorable outcomes have been obtained in high-risk patients treated with CAS, 30) procedure-related ischemic complications such as cerebral embolism 11,18) and acute stent thrombosis 10) have been reported. Dual antiplatelet therapy has been recommended to prevent these ischemic complications.…”
Section: Introductionmentioning
confidence: 99%